2021
DOI: 10.17221/11/2021-pse
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of soil organic matter composition under different land uses by DRIFT spectroscopy

Abstract: The study aimed to estimate and characterise soil organic matter under different land uses (cropland, grassland, and forest) and soil depths. The soil organic matter composition of the soil was assessed by diffuse reflectance infrared spectroscopy (DRIFT). Humic and fulvic acids (HAs, FAs) were extracted from soils and their compositions were evaluated by DRIFT. Low molecular mass organic acids content was also measured. Our result revealed that the largest differences of the spectra in the composition of orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Yao et al (2019) also observed that aromatic CC groups were higher in the SOM from three cultivated areas than in native grasslands. Aliphatic CH was also observed to be more concentrated under the tree line than tillage operations (Table 2), which is consistent with that of Thai et al (2021), who found that forest soil spectra have more intense aliphatic bands than the spectra of cropland soils. Moreover, Schnitzer et al (2006) reported an increase in aromatics and a decrease in SOM aliphatic content with increasing cultivation intensity.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Yao et al (2019) also observed that aromatic CC groups were higher in the SOM from three cultivated areas than in native grasslands. Aliphatic CH was also observed to be more concentrated under the tree line than tillage operations (Table 2), which is consistent with that of Thai et al (2021), who found that forest soil spectra have more intense aliphatic bands than the spectra of cropland soils. Moreover, Schnitzer et al (2006) reported an increase in aromatics and a decrease in SOM aliphatic content with increasing cultivation intensity.…”
Section: Discussionsupporting
confidence: 90%
“…Several parameters affect SOM composition, including the decomposition rate, types of plant residues, soil texture, microbiological composition, chemical and mineralogical composition, and climatic conditions such as temperature and moisture content (Lal, 2018; Thai et al, 2021). In addition, artificial effects, such as physical disturbance, and land use may also determine SOM composition (Abera & Belachew, 2011; Adiyah et al, 2022; Alam et al, 2014; Cao et al, 2011; Helfrich et al, 2006; Qin et al, 2016; Yu et al, 2015; Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the darkness of forest soil samples, the spectra were recorded by 120 scans in wavenumbers ranging from 4000 to 400 cm −1 at a resolution of 4 cm −1 . The measured reflectance was converted to Kubelka-Munk units (KM), and the gold mirror was used as the background of the spectra (Thai et al 2021). The potential wettability index (PWI), aromaticity index (iAR), and decomposition index (iDEC) were determined using DRIFT spectra.…”
Section: Diffuse Reflectance Infrared Fourier Transform Spectroscopymentioning
confidence: 99%
“…In mixtures of substances such as soil, identification of individual molecules is difficult because the spectral bands of the organic and mineral components of the soil may overlap. Although mid-IR spectroscopy has its limits given the complexity of the soil, it detects the presence of important functional groups of SOM, and thus it can provide information about relative differences in SOM composition in different soil types and soil horizons (Pavlů et al 2023) or for example in different land use (Thai et al 2021).…”
mentioning
confidence: 99%